Entrepreneurship Orientation as Antecedent of Family Business Performance - Kurniawan, Daniel (Jurnal Entrepreneur dan Entrepreneurship, 2020)
Abstract The performance of a family business has become an interesting issue on the family business research. On the other hand, how to achieve that goal is still arguable. Based on literature review, entrepreneurship orientation is one of the key predictors for family business performance. This study took sample of 201 medium family company in Surabaya. Purposive sampling is selected as sample technique. The findings of this study imply entrepreneurship orientation significantly positive correlate to family business performance. Keywords: entrepreneurial orientation, family business performance, family business